Evaluating pay-as-you-go social security systems - Andreas Bachmann; Kaspar Wüthrich (University of Bern, Department of Economics, 2013)
This paper proposes a new method for welfare analysis of unfunded social security systems. Based on an overlapping generations model with endogenous labor supply, we derive a formula for the evaluation of existing pay-as-you-go social security systems that depends on impulse response functions and projected growth rates only. We propose an implementation strategy based on reduced form estimates of a VAR model that is valid under weak assumptions about the deep structure of the model. Our method is related to the sufficient statistic approach (Chetty, 2009). For the current system in the United States, we find that a transitory increase in the payroll tax rate along with higher pension benefits leads to a welfare increase mainly due to welfare gains of today's retirees. A scenario analysis demonstrates the robustness of this result.
Keywords: E62; H55; 330; unfunded social security system; sufficient statistic; overlapping generations; reduced form VAR